Inspection method of surface film

The use of fluoride ions in a test solution accelerates corrosion damage on chemical conversion coatings, enabling rapid visual inspection and timely feedback to manufacturing processes.

JP2025065639APending Publication Date: 2025-04-22MITSUBISHI HEAVY IND LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023174979
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Conventional corrosion resistance testing methods for chemical conversion coatings on metal surfaces, such as salt spray testing, require several days to provide results, making it difficult to provide timely feedback to manufacturing processes.

Method used

A testing method using an aqueous solution containing fluoride ions to accelerate damage to chemical conversion coatings, allowing for rapid visual inspection of corrosion resistance within a short period, typically 48 hours or less.

Benefits of technology

Enables rapid visual detection of corrosion damage, facilitating timely correction of manufacturing processes by distinguishing between conforming and non-conforming products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065639000001_ABST
    Figure 2025065639000001_ABST
Patent Text Reader

Abstract

To provide a test method that can timely give feedback to a manufacturing process when a test piece is determined to be a nonconforming item, and contribute to promptly preventing the nonconforming item from being continuously manufactured.SOLUTION: An inspection method of a surface film includes a first step of preparing a test liquid consisting of an aqueous solution containing fluoride ions and a second step of immersing a test piece in the prepared test liquid. The test piece is a metallic member with a surface on which a chemical film is formed. Preferably, the test liquid contains hydrogen fluoride as a supply source of fluoride ions. Preferably, the test piece is the metallic member with the surface on which a chromate film is applied. Preferably, the metallic member is an aluminum alloy.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for inspecting a surface film that is suitable for inspecting the quality of a chemical conversion film applied to, for example, an aluminum alloy. [Background technology]

[0002] To increase the corrosion resistance of metal materials such as aluminum alloys, a chemical conversion coating is sometimes applied to the surface. For example, chromate-treated aluminum alloys are widely used in the aircraft industry. Inspection is sometimes required to ensure the quality and integrity of such chemical conversion coatings. Salt spray testing (JIS Z2371) is often carried out as a quality inspection of chemical conversion coatings. In salt spray testing, a test piece is placed in a salt spray testing device that is kept at a constant temperature, and a mist of sodium chloride solution is sprayed onto it. The surface condition of the test piece is observed after a specified period of time has passed since the spraying, but the test period generally requires more than several days.

[0003] Patent Document 1 proposes a test method in which the test liquid is an aqueous solution containing sodium ions, chloride ions, and sulfate ions in order to simulate a real environment more accurately than the salt spray test. Patent Document 1 also discloses that in addition to the above three types of ions, the test liquid may further contain magnesium ions and calcium ions, and may further contain potassium ions, strontium ions, bromine ions, bicarbonate ions, fluoride ions, and boric acid. However, according to the examples in Patent Document 1, a 240-hour combined cycle test CCT-N2 (Non-Patent Document 1) is required, which is the same in that a test period of more than several days is required. The objects inspected in the examples in Patent Document 1 are steel sheets and zinc sheets. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6713972 [Non-Patent Document 1] Takashi Miwa et al., "Comparison of corrosion behavior of steel and zinc under various accelerated corrosion test conditions," Rust Prevention Management, Vol. 60, No. 1, pp. 7-14, 2016. Summary of the Invention [Problem to be solved by the invention]

[0005] Corrosion resistance testing methods such as the salt spray method generally require a test period of more than several days. Therefore, even if the results of the salt spray method indicate that a product is non-compliant, it is difficult to provide feedback to the manufacturing process in a timely manner. Based on the above, the present disclosure proposes a testing method that can obtain inspection results in a shorter time than the conventional salt spray method, and that can provide timely feedback to the manufacturing process when non-conforming products are identified, quickly correcting the continued production of non-conforming products. [Means for solving the problem]

[0006] The inspection method according to the present disclosure includes: Preparing a test solution comprising an aqueous solution containing fluoride ions; and a step of immersing the test object in the prepared test liquid. The object to be inspected is an aluminum alloy having a chemical conversion coating formed thereon. Effect of the Invention

[0007] According to the present disclosure, by using a test solution containing fluoride ions, which are more likely to cause damage to a chemical conversion coating than the chloride ions contained in sodium chloride, it is possible to obtain visually observable test results in a short period of time. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a flow diagram showing a procedure of an inspection method according to an embodiment of the present disclosure. [Diagram 2] FIG. 1 is a flow chart showing the procedure of a preliminary test for determining in advance the conditions of a test solution that can clearly distinguish between conforming and non-conforming products. [Diagram 3] 11 is a photograph showing an inspection result according to the embodiment. [Figure 4] Photographs showing the results of immersing the same test specimen in an aqueous NaCl solution used in the salt spray method. [Diagram 5] FIG. 13 is a diagram showing an image of the effect achieved by an embodiment of the present disclosure. [Figure 6] FIG. 1 is a diagram for explaining the effect when copper (Cu) ions are added to a test liquid. [Figure 7] 1 is a photograph showing the effect of adding copper (Cu) ions to a test solution. [Figure 8] 13 is a photograph showing an example of determining conformity or non-conformity based on glossiness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, embodiments will be described with reference to the accompanying drawings. [Summary of the inspection method] The surface film inspection method according to the embodiment uses an aqueous solution containing fluoride ions as a test liquid. The method is based on the finding that fluoride ions have the effect of promoting the pitting phenomenon, which is damage to chemical conversion films. Here, the fluoride ions are negative ions (F - ) As fluoride ions, hydrogen fluoride (HF), sodium fluoride (NaF), etc. are applied to the inspection method of the present disclosure. In particular, it is desirable to use an aqueous solution containing hydrogen fluoride as the test liquid in order to lower the pH (potential hydrogen) of the test liquid and promote damage to the chemical conversion coating. Note that pH is expressed as a value from 0 to 14, with pH=7 being neutral, pH less than 7 being acidic, and pH greater than 7 being alkaline. Therefore, a test liquid containing hydrogen fluoride will be more acidic.

[0010] In the salt spray test, sodium chloride contained in the test liquid accelerates damage to the chemical conversion film, but it takes a test period of several days or more for the damage to progress to a visible state. In this embodiment, fluoride ions, which are more likely to cause damage to the chemical conversion film than chloride ions contained in sodium chloride, are used in the test liquid, making it possible to visually confirm the test results in a short period of time.

[0011] [Test piece: object to be inspected] The test piece, which is the object to be inspected in this embodiment, is a metal member having a chemical conversion coating formed on its surface. Metal materials are classified into ferrous metals and non-ferrous metals, and the present embodiment is applicable to both. However, in the case of chromate treatment of ferrous metals, it is applied on a plating film made of a non-ferrous metal such as zinc.

[0012] Chemical conversion coating is a general term for inorganic coatings that are chemically deposited on metal surfaces by immersion in a treatment solution. Phosphate treatment and chromate treatment are well-known methods for forming chemical conversion coatings, and the present disclosure can be applied to the inspection of both types of chemical conversion coatings, but is preferably applied to chemical conversion coatings formed by chromate treatment. The inspection method of the present disclosure is applied to ensure the soundness of the chemical conversion coating.

[0013] [Phosphate Salt Treatment] Phosphating is a process in which the surface of a metal base material is corroded and dissolved while a phosphate film is deposited on the surface through a chemical reaction. Phosphating is a technology that was originally established for iron-based metal materials. Among the various types of phosphate treatment, zinc phosphate treatment is applied to zinc materials such as zinc-plated steel sheets and zinc die castings, as well as aluminum materials such as aluminum alloy sheets and aluminum die castings.

[0014] [Chromate Treatment] Chromate treatment is an example of a chemical conversion treatment used for non-ferrous metals such as aluminum alloys, zinc alloys, and magnesium alloys. In this disclosure, for example, when referring to an aluminum alloy, it means not only aluminum alloys but also pure aluminum. The same applies to zinc, magnesium, etc. After chromate treatment, the surface of the metal is covered with an oxide film (chromate film) that contains chromium, which has a barrier effect that prevents corrosion and can extend the life of the metal component.

[0015] [Test procedure: See Figure 1] The inspection procedure according to this embodiment is carried out in the following order: determining the components and concentrations of the test liquid (S101 in FIG. 1), preparing the test liquid (S103 in FIG. 1), immersing a test piece that has been subjected to a chemical conversion coating treatment in the test liquid (S105 in FIG. 1), maintaining the immersion for a specified period of time (S107 in FIG. 1), inspecting the appearance (S109 in FIG. 1), and assessing the quality of the chemical conversion coating (S111 to S117 in FIG. 1).

[0016] [Figure 1 S101, S103] The test liquid in this embodiment is an aqueous solution containing fluoride ions that promote damage to the chemical conversion coating. Here, the fluoride ions are anions (F - ) The concentration of fluoride ions contained in the test liquid is selected from the range of 0.01 to 100 g / L, preferably from the range of 0.5 to 50 g / L, and more preferably from the range of 1 to 10 g / L. Ions that may be contained in addition to fluoride ions are ions of metal elements that have a lower ionization tendency than the main component metal elements of the base material, as described below, but other ions are permitted to be contained in a total amount of up to 50 g / L.

[0017] In step S101 for determining the test solution components and concentrations, the inspection sensitivity of the conversion coating can be controlled by changing the fluoride ion concentration in the test solution. In other words, the conditions of the test solution (liquid components and concentration) that can clearly distinguish between conforming and non-conforming products are determined in advance through preliminary testing according to the specifications of the conversion coating to be manufactured. This procedure is shown in Figure 2. By following this procedure, quality inspection can be carried out according to the specifications of the conversion coating to be inspected.

[0018] In this embodiment, it is preferable to use hydrogen fluoride as a supply source of fluoride ions. Here, in particular, the pH of the solution can be lowered to promote damage to the chemical conversion coating. Note that pH is expressed as a value from 0 to 14, with pH=7 being neutral, a value less than 7 being acidic, and a value greater than 7 being alkaline. Therefore, a test solution containing hydrogen fluoride has a high degree of acidity.

[0019] In this embodiment, in order to improve visual visibility, the test liquid may contain ions of metal elements that have a smaller ionization tendency than the main component metal elements of the base material. The ionization tendency is a measure of the tendency of a metal to become a cation in a solution (mainly an aqueous solution). A metal that is likely to become a cation means that it is likely to release electrons, and a metal that is not likely to become a cation means that it is likely to receive electrons. The test piece is made of an aluminum alloy. It is known that the metal elements with a smaller ionization tendency than Al are Zn, Fe, Ni, Sn, Pb, Cu, Hg, Ag, Pt, and Au, in that order, but among these, the metal elements that can be practically used are narrowed down, taking into account issues such as cost and handling. Among them, it is preferable to use metal ions with a different color from the aluminum alloy and the chromate film, specifically Cu ions. The concentration of these ions is preferably in the range of 0.001 to 200 g / L, more preferably in the range of 0.01 to 100 g / L, and even more preferably in the range of 1 to 10 g / L. The specific effects of including Cu ions in the test solution will be described later.

[0020] [Figure 1 S105, S107] After the test liquid has been prepared, the test piece is immersed in the test liquid and held there for a predetermined period of time. By using the test liquid of this embodiment, it is possible to obtain a damage state that can withstand visual inspection of the test piece even if the predetermined immersion time is shortened. Specific examples of the damage state will be described later. According to the study by the present inventor, the immersion time of the test piece is 48 hours or less, preferably 12 hours or less, and more preferably 6 hours or less. When speed is particularly required, immersion times of 1 hour or less can distinguish between conforming and non-conforming products. The immersion time is determined according to the material of the test piece, the surface condition, and other conditions.

[0021] A method for accelerating damage to the chemical conversion coating can be taken for the test liquid in which the test piece is immersed. Typically, this involves heating the test liquid to a temperature above room temperature. Since the test liquid is an aqueous solution, specific methods for heating the test liquid include a method using a liquid that has been heated to a temperature above room temperature in advance, a method using a water bath with a temperature control function, and a method using a thermostatic bath.

[0022] [Figure 1 S109, S111, S113, S115] After the test piece has been immersed for the specified time, it is removed from the test solution and subjected to a visual inspection. Based on the results of the visual inspection, it is determined whether the conversion coating satisfies the quality standards. The appearance inspection and judgment may be performed by applying one or both of a method based on human visual inspection and a method other than human visual inspection. For example, in the former case, judgment can be performed by comparing the color tone of a color sample with that of the test piece. In the latter case, the glossiness of the surface of the test piece can be measured and the measured glossiness can be compared with a glossiness threshold value that serves as the judgment criterion. In the latter case, quantitative judgment can be performed. A specific example of measuring glossiness will be described later.

[0023] If the test piece is determined to conform to the quality standard, the result of the determination is stored, for example. If the test piece is judged as not conforming to the quality standard as a result of the judgment, the judgment result is reflected in improvements to the manufacturing process that has been carried out up to that point, in this case the process of forming the chemical conversion coating.

[0024] [Example 1] Five test pieces made of an aluminum alloy (JIS A2024, super duralumin) on which a chromate film was formed were immersed in the test solution according to this embodiment to confirm the effect. The results are shown in Figure 3. The five test pieces had different qualities of chromate film before being immersed in the test solution, and the "average SST pit number" in Figure 3 indicates these differences. The "average SST pit number" is the number of pits counted after a conventional salt spray test was performed on the same test pieces as the five test pieces, and the higher the "average SST pit number", the lower the quality of the chromate film. Test solution: Ingredients / concentration: Fluoride ion 5g / L (aqueous solution) Temperature; 25℃

[0025] The results of immersing the same test piece in the NaCl aqueous solution used in the salt spray method (conventional example) are shown in Figure 4. The test piece used in this conventional example had an "average SST pit count" of about 300, indicating that the quality of the chromate film was extremely low. Test solution: Ingredients / concentration: Chloride ion 20g / L (aqueous solution) Temperature; 25℃

[0026] See Figure 3. Even in the case of a test piece with one pit, which represents the best quality of the chromate film, parts with different color tones are visible after only 90 minutes of immersion, and damage can be visually recognized. In the case of a test piece with 112 pits, which represents the worst quality of the chromate film, damage can be visually recognized after 30 minutes of immersion. See Figure 4. When immersed in salt water, the surface appearance of all test pieces exhibited a metallic luster before and after 30 minutes of immersion, with no difference apparent.

[0027] [Effects of Example 1: see FIG. 5] By detecting the color change when a test piece is immersed in an aqueous solution containing fluoride ions, it is possible to determine whether a product is compliant or non-compliant. Because the test results can be obtained in a shorter time than with the test fluids used in the conventional salt spray method, when non-conforming products are discovered, the information can be fed back in a timely manner to improve the manufacturing process, specifically the conditions of the chemical coating treatment, making it possible to quickly correct the continued production of non-conforming products.

[0028] [Example 2] Copper (Cu) ions were added to the test liquid used in Example 1, and a test was carried out in the same manner as in Example 1. Test liquid: Aqueous solution Ingredients / concentration: Fluoride ion 5g / L, Copper (Cu) ion 5g / L Temperature; 25℃

[0029] Fluoride ions accelerate damage to the chemical conversion coating, and the potential difference between the base metal (aluminum alloy) and the chemical conversion coating causes copper to precipitate in the pits, resulting in a change in color, as shown in Figure 6. Note that Figure 6 explains one pit, but if multiple pits exist over the entire area of ​​the chemical conversion coating, copper will also precipitate over the entire area of ​​the chemical conversion coating. The test results are shown in Figure 7. By using a test solution containing copper (Cu) ions, the visibility of the test results is improved, thereby improving the reliability of quality assessment.

[0030] [Example 3] In judging the quality based on the results of the immersion test, the change in color tone of the surface of the test piece can be confirmed visually, but if a quantitative judgment is required, it can be judged, for example, by the specular gloss specified in JIS Z 8741. For example, if the standard value for specular gloss is determined to be in the range of 5 to 20, a product can be judged as conforming if the measured specular gloss is equal to or greater than the standard value, and as non-conforming if it is less than the standard value. The quantitative evaluation results are shown in Figure 8. The conforming product had little copper precipitation during the immersion test, and so had a high gloss of 88. On the other hand, the non-conforming products had a low gloss of 0.4 to 0.6 due to copper precipitation, regardless of the number of pits on the test piece.

[0031] For quantitative judgment, in addition to specular gloss, color tone and color difference can also be used as judgment criteria. Color tone can be determined by analyzing the RGB values ​​of a photograph taken of the surface of the test piece, and color difference can be measured with a color difference meter. In addition, when copper precipitates on the surface as in Example 2, it is possible to quantitatively judge whether a product is conforming or non-conforming by measuring the amount of Cu present. The amount of Cu present is measured by X-ray analysis, etc.

[0032] [Note] The inspection method disclosed above can be understood as follows. [Appendix 1] The surface film inspection method is as follows: A first step of preparing a test solution comprising an aqueous solution containing fluoride ions; A second step of immersing a test piece in the prepared test liquid, The test piece is a metal member having a chemical conversion coating formed on the surface thereof. [Appendix 2] In Appendix 1, preferably, The test solution is The source of the fluoride ions includes hydrogen fluoride. [Appendix 3] In addition 1 or addition 2, preferably The test piece is The metal member has a chromate film applied to its surface. [Appendix 4] In any one of Supplementary Note 1 to Supplementary Note 3, preferably, The metal member is an aluminum alloy. [Appendix 5] In any one of Supplementary Notes 1 to 4, preferably, The test solution is The metal member contains ions of a metal element having a smaller ionization tendency than the main metal element of the metal member. [Appendix 6] In Supplementary Note 5, preferably, The metal element ion is a copper (Cu) ion. [Appendix 7] In any of Supplementary Note 1 to Supplementary Note 6, Preferably, the test liquid is heated to a temperature above room temperature. [Appendix 8] In any of Supplementary Note 1 to Supplementary Note 6, The method includes a third step of determining a damage state of the chemical conversion coating of the test piece that has been immersed in the test liquid for a predetermined time in the second step. [Appendix 9] In Appendix 8: The determination of the damage state in the third step includes: It is carried out quantitatively based on measurements taken on the surface of the test specimen. [Appendix 10] In Appendix 9: The measured value is gloss.

[0033] In addition to the above, it is possible to select and discard the configurations given in the above embodiment, or to change them to other configurations as appropriate.

Claims

1. A first step of preparing a test liquid comprising an aqueous solution containing fluoride ions; A second step of immersing a test piece in the prepared test liquid, The method for inspecting a surface film, wherein the test piece is a metal member having a chemical conversion film formed on its surface.

2. The test solution is The source of fluoride ions includes hydrogen fluoride. The method for inspecting a surface film according to claim 1.

3. The test piece is The metal member has a surface coated with a chromate film. The method for inspecting a surface film according to claim 1.

4. The metal member is an aluminum alloy. The method for inspecting a surface film according to claim 3.

5. The test solution is containing ions of a metal element having a smaller ionization tendency than the main metal element of the metal member, The method for inspecting a surface film according to claim 1.

6. The metal element ion is a copper (Cu) ion. The method for inspecting a surface film according to claim 5.

7. The test liquid is heated to a temperature above room temperature. The method for inspecting a surface film according to claim 1.

8. a third step of determining a damage state of the chemical conversion coating of the test piece immersed in the test liquid for a predetermined time in the second step; The method for inspecting a surface film according to claim 1.

9. The determination of the damage state in the third step includes: Quantitatively based on measurements obtained on the surface of the test piece, The method for inspecting a surface film according to claim 8.

10. The measurement is specular gloss. The method for inspecting a surface film according to claim 9.

Citation Information

Patent Citations

  • Test solutions for accelerated corrosion tests

    JP6713972B2